2023
DOI: 10.1097/qco.0000000000000975
|View full text |Cite
|
Sign up to set email alerts
|

Treatment approaches for severe Stenotrophomonas maltophilia infections

Maria F. Mojica,
Robert A. Bonomo,
David van Duin

Abstract: Purpose of review Stenotrophomonas maltophilia is an emerged opportunistic pathogen. Intrinsic multidrug resistance makes treating infections caused by S. maltophilia a great clinical challenge. Herein, we provide an update on the most recent literature on treatment options for severe S. maltophilia infections. Recent findings Trimethoprim-sulfamethoxazole (SXT) is recognized as the first-line therapy for S. maltophilia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 144 publications
0
7
0
Order By: Relevance
“…According to our study, while in the U.S., a high level of treatment success is achieved with any of the three dose regimens studied (CFR ≥ 90%), in Europe, even with the highest dose evaluated, the probability of treatment success is much lower (CFR < 75%). In spite of our results, and despite the fact that a recent meta-analysis has shown that the resistance rate of S. maltophilia has increased in recent years [ 24 ], cotrimoxazole remains the first choice for treatment, with the dosing recommendation ranging from 10 to 15 mg/kg/day of trimethoprim q8h and a maximum daily dose of trimethoprim of 960 mg [ 1 , 8 ].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…According to our study, while in the U.S., a high level of treatment success is achieved with any of the three dose regimens studied (CFR ≥ 90%), in Europe, even with the highest dose evaluated, the probability of treatment success is much lower (CFR < 75%). In spite of our results, and despite the fact that a recent meta-analysis has shown that the resistance rate of S. maltophilia has increased in recent years [ 24 ], cotrimoxazole remains the first choice for treatment, with the dosing recommendation ranging from 10 to 15 mg/kg/day of trimethoprim q8h and a maximum daily dose of trimethoprim of 960 mg [ 1 , 8 ].…”
Section: Discussionmentioning
confidence: 91%
“…These results agree with Lasko et al [ 18 ], who demonstrated that cotrimoxazole in monotherapy even at a high dose displays limited activity against cotrimoxazole-susceptible S. maltophilia strains. In fact, several authors have pointed out the necessity of redefining the breakpoints of cotrimoxazole for S. maltophilia [ 8 , 19 , 20 ]. Apart from cotrimoxazole, we detected discrepancies between the breakpoints for the rest of the antibiotics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of S. maltophilia infections in the hospital setting has been on the rise, and this bacterium is increasingly recognized as a formidable multidrug-resistant pathogen . Traditionally, S.…”
Section: Introductionmentioning
confidence: 99%
“… 20 The prevalence of S. maltophilia infections in the hospital setting has been on the rise, and this bacterium is increasingly recognized as a formidable multidrug-resistant pathogen. 21 Traditionally, S. maltophilia has demonstrated resistance to a wide range of β-lactam antibiotics, including penicillins, cephalosporins, and carbapenems. This resistance is primarily attributed to the expression of L1 and L2 β-lactamases.…”
Section: Introductionmentioning
confidence: 99%